Where did the money go? Endogenous money creation for international fraudulent purposes: the case of the 2015 Moldovan banking scandal. (2015) - Pilkington, Marc
We investigate the biggest banking scandal ever in the History of the Republic of Moldova, based on the Kroll Report published in 2015, which focuses on three commercial banks that account for a third of the country's banking sector. Firstly, we present a brief synopsis of the 2015 Moldovan banking scandal. Secondly, we investigate the under-explored issues of corporate governance structures of both lenders and borrowers as well as the impact of transnational financial engineering practices in the context of endogenous money theory. Finally, we sketch out the implications of the 2015 Moldovan banking scandal for post-Keynesian monetary theory by, on the one hand, rehabilitating the concept of endogenous finance, and on the other hand, by demonstrating how the scandal is best conceptualised by elaborating a new framework focusing on the interface between transnational financial elites and the shadow banking system in transition economies.